Veritable Mobile Phone Applications for Affecting the Exchange of Agricultural Information among Farmers in Tanzania - Mtega, Wulystan Pius (University of Dar es Salaam Library Journal, 2021)
The importance of mobile phones in communication cannot be overemphasized. This study investigated farmers ' usage of mobile phones in exchanging agricultural information. Specifically, it compared the level of usage of mobile phones and other communication channels in exchanging agricultural information among farmers; found out the most usable mobile phone applications for exchanging agricultural information among farmers, and determining factors influencing the usage of mobile phones in exchanging agricultural information. The study was guided by the Task-Technology Fit model. A sample of 188 farmers owning mobile phones was purposively selected. A structured questionnaire and a focus discussion guide were used for collecting data. Content analysis and SPSS software were used for analysing data. Results indicate that mobile phone calls and SMS were mostly used by farmers. The limited power supply in rural areas, unaffordable mobile phone tariffs, and poor mobile phone infrastructure in rural areas were mentioned to lower the usage of mobile phones in exchanging agricultural information. The study concludes that when used efficiently, mobile phones have the potential of transforming the agricultural sector. It is recommended that mobile phone service providers should reduce the costs of their services for more farmers to use them.